1995
DOI: 10.1007/bf00005919
|View full text |Cite
|
Sign up to set email alerts
|

Ecomorphological diversification and convergence in fluvial cichlid fishes

Abstract: SynopsisWe compared ecological and morphological patterns among cichlid faunas from three different biotic regions : the Rfo Tortuguero/Rio Sarapiquf in Costa Rica, the Rfo Apure drainage in Venezuela, and the Upper Zambezi drainage in Zambia . Cichlids comprise 19 percent of the fish fauna in the Tortuguero and Upper Zambezi drainages and 6 .5 percent in the Apure drainage. Cichlid faunas exhibited similar patterns of habitat and food resource utilization, although vegetation-dwelling is more common and detri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
0
9

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(196 citation statements)
references
References 49 publications
7
179
0
9
Order By: Relevance
“…3). Benthic fishes from the algivorous and mud feeder guilds were also characterized by relatively narrow heads and a ventral (Loricaridae) or oblique (Curimatidae) mouth orientation and this result is again well supported by other studies (Gatz 1979;Watson and Balon 1984;Winemiller et al 1995;Hugueny and Pouilly 1999;Pouilly et al 2006). Fishes from the herbivorous and piscivorous guilds generally displayed a large standard length while species from the aquatic invertivorous guild were mostly characterized by their small sizes.…”
Section: Relationships Between Diet and Morphologysupporting
confidence: 82%
See 1 more Smart Citation
“…3). Benthic fishes from the algivorous and mud feeder guilds were also characterized by relatively narrow heads and a ventral (Loricaridae) or oblique (Curimatidae) mouth orientation and this result is again well supported by other studies (Gatz 1979;Watson and Balon 1984;Winemiller et al 1995;Hugueny and Pouilly 1999;Pouilly et al 2006). Fishes from the herbivorous and piscivorous guilds generally displayed a large standard length while species from the aquatic invertivorous guild were mostly characterized by their small sizes.…”
Section: Relationships Between Diet and Morphologysupporting
confidence: 82%
“…carla.lunallena@gmail.com;oberdorf@mnhn.fr Winemiller et al 1995;Piet 1998;Hugueny and Pouilly 1999;Xie et al 2001;Elliott and Bellwood 2003;Pouilly et al 2003). For instance, in fishes, gut length clearly distinguish algivores, detritivores and herbivores from carnivores (Paugy 1994;Kramer and Bryant 1995;Delariva and Agostinho 2001;Ward-Campbell et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between body shape and resource use may be related to the evolutionary history of the species (Winemiller, 1991). Thus, morphological patterns in assemblages tend to characterize species groups that explore the same ecological resource -e.g., species in the same trophic guild may present a higher morphological similarity, independently of their phylogenetic distance , since the exploitation of specific food items in an ecosystem can be facilitated by a specific design (Wootton, 1992;Norton & Brainerd, 1993;Gerking, 1994;Norton, 1995;Winemiller, et al, 1995;Montaña & Winemiller, 2009;Sampaio et al, 2013). For this reason, some authors attribute to the morphology the ability to predict the ecological niche -i.e., how the body shape selects the ecological space in a given habitat, and consider that ecomorphology can be used as a tool in analysis of assemblage structure (Winemiller, 1991;Casatti & Castro, 2006;Oliveira et al, 2010;Pagotto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ecomorphological patterns were aIso investigated for fish communities of Canada and Europe (MAHON, 1984), Bornéo (WATSON & BALON, 1984), Sri Lanka (MOYLE & SENANAYAKE, 1984 ;WIKRAMANAYAKE, 1990), and Florida (MOTTA et al, in press). LAUDER (1983) integrated ecomorphology with phylogeny to examine evolutionary patterns of niche divergence in North American sunfishes, and WINEMILLER WINEMILLER et al, in press) examined patterns of ecomorphological convergence and divergence in local assemblages from différent biotic régions. Ecomorphological comparisons of faunal structure use morphology as a surrogate for ecological performance and rely heavily of inferences from functional morphology.…”
Section: Morphological Diversitymentioning
confidence: 99%
“…Interspecific trophic diversity has been investigated from the standpoints of assemblage structure and species interactions (e.g., FRYER, 1959 ;GOULDING, 1980 ;GOULDING et al, 1988 ;WINEMILLER & PIANKA, 1990) and evolutionary divergence within phylogenetic clades (YAMAOKA, 1982 ;WINEMILLER, 1991 ;WINEMILLER et al, in press). Patterns of food resource utilization in fish communities have shown a large degree of diet overlap in most Systems (ROSS, 1986), but some studies have demonstrated diet shifts in response to competitors (WERNER, 1977 ;CROWDER, 1986 ;ROBINSON & WILSON, 1994) or temporally varying resource availability (e.g., ZARET & RAND, 1971 ;GOULDING, 1980 ;WINEMILLER, 1989b).…”
Section: Venezuela-!mentioning
confidence: 99%